2002
DOI: 10.1097/00001703-200210000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Sacral neuromodulation: new applications in the treatment of female pelvic floor dysfunction

Abstract: While the data are encouraging in these new arenas of pelvic floor disorders, investigators acknowledge the need for multicenter, statistically powered studies to evaluate the validity of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…A number of randomized, multi-center trials have demonstrated the e¡ectiveness and durability of sacral neuromodulation in the treatment of refractory voiding dysfunction [Schmidt et al, 1999;Hassouna et al, 2000;Siegel et al, 2000;Janknegt et al, 2001]. Furthermore, the role of sacral neuromodulation in treating other pelvic £oor disorders including interstitial cystitis, pelvic pain syndromes, and bowel dysfunction have shown encouraging results but require statistically powered multi-center trials with longer follow up [Pettit et al, 2002;Bernstein and Peters, 2005]. As indications for SNS continue to expand, it is likely that pelvic neuromodulation will continue to play an integral role in the management of a variety of refractory voiding disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of randomized, multi-center trials have demonstrated the e¡ectiveness and durability of sacral neuromodulation in the treatment of refractory voiding dysfunction [Schmidt et al, 1999;Hassouna et al, 2000;Siegel et al, 2000;Janknegt et al, 2001]. Furthermore, the role of sacral neuromodulation in treating other pelvic £oor disorders including interstitial cystitis, pelvic pain syndromes, and bowel dysfunction have shown encouraging results but require statistically powered multi-center trials with longer follow up [Pettit et al, 2002;Bernstein and Peters, 2005]. As indications for SNS continue to expand, it is likely that pelvic neuromodulation will continue to play an integral role in the management of a variety of refractory voiding disorders.…”
Section: Discussionmentioning
confidence: 99%
“…There are several explanations for this observation. First of all, there is a 16.4% long-term failure rate with a staged implant, which may be due to an initial placebo e¡ect during the test stimulation period [Pettit et al, 2002]. As a result, the optimal screening period has not yet been de¢nitively determined, but most studies use a period of 7^14 days.…”
Section: Discussionmentioning
confidence: 99%
“…urinary incontinence, urgency-frequency syndromes and unobstructive urinary retention, translate into a significant burden both in cost and quality-of-life issues for women and men. Sacral nerve stimulation (SNS) involves the stimulation of the sacral nerves to modulate the neural reflexes that influence the bladder, urethral sphincter and pelvic floor [1]. In the early 1980s, the work of Schmidt and Tanagho [2,3] showed that electrical stimulation of the sacral nerve root could reduce inappropriate neural activity, thereby inhibiting the overactive detrusor.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of sacral nerves, specifically S3 has shown results for urinary incontinence secondary to detrusor hyper relfexia, interstitial cystitis, faecal incontinence and in refractory pelvic pain conditions [14]. The selection criteria and methodology of implantation is addressed more elaborately in specific literature.…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%